Sono-electroanalysis: Application to the detection of lead in wine - Akkermans, R; Ball, J; Rebbitt, T; Marken, F; Compton, R (1998)
The quantitative detection of lead in wine is shown to be possible by anodic stripping voltammetry under conditions of insonation. An immersion horn probe is introduced into a thermostatted conventional three-electrode cell opposite a mercury plated platinum disc working electrode. Following acidification of the wine sample lead ions can be reduced at the Hg/Pt electrode surface at -1.0 V (vs SCE). The large mass transport associated with power ultrasound yields efficient pre-concentration of the lead before it is stripped by an anodic linear sweep of the potential. Insonation further offers the crucial benefits of first surface activation and cleaning, helping to prevent electrode fouling by the organic components in wine and second fully equilibrating "free" and "bound" Pb2+ ions in the complex matrix. By use of standard microaddition of lead to the solution the system can be calibrated to give the total amount of lead present. Experiments using samples of a white Italian Chardonnay gave a total lead content of 22 ± 6 μg 1-1. This value was compared with those obtained by independent atomic absorption spectroscopy (AAS) measurements performed by two different laboratories. Quantitative agreement was found. © 1998 Elsevier Science Ltd. All rights reserved.